2020
DOI: 10.1177/1753466619898598
|View full text |Cite
|
Sign up to set email alerts
|

Airway wall thickness and airflow limitations in asthma assessed in quantitative computed tomography

Abstract: Background: Asthma is a frequent chronic disease of the airways. In spite of the fact that symptoms of asthma are well known, the pathogenesis has not yet been fully understood. Quantitative computed tomography (qCT) of the lung allows for the measurment of a set of parameters. The aim of this study was to evaluate the usefulness of quantitative computed tomography in the assessment of airway wall thickness in asthma. Methods: The prospective study was performed on a group of 83 patients with well-defined, lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 18 publications
2
18
0
Order By: Relevance
“…The full methodology of CT scanning, lung function testing, and statistical analysis were described in the associated publication: Patyk M. et al (2020) [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…The full methodology of CT scanning, lung function testing, and statistical analysis were described in the associated publication: Patyk M. et al (2020) [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Thanks to the development of high-resolution CT scanners and advanced reconstruction techniques it is now possible to visualise airways in the range of 1 mm in diameter using low-dose protocols. CT images acquired during a breath hold at full inspiration can provide detailed information on airway generation and airway wall dimensions (figure 3) [138]. In operated patients with COPD it was shown that airway size measured by pre-operative CT correlated to airway size as measured histologically [139].…”
Section: Static Imagingmentioning
confidence: 99%
“…In asthma it was shown that the airway walls, as measured on CT, were thicker compared to healthy subjects. Furthermore, it was shown that increased airway wall thickness observed on CT was related to lower forced expiratory volume in 1 s and higher risk of exacerbations [138,140]. Static CT images acquired during expiration can show regions of low attenuation that are thought to reflect SAD (figure 2).…”
Section: Static Imagingmentioning
confidence: 99%
“…More details of the computed tomography scanning protocol, measuring of the bronchial tree features are described in Patyk et al (2020) study [12].…”
Section: Quantitative Computed Tomographymentioning
confidence: 99%
“…The influence of airway remodeling on lung function is postulated, and the relationship is still under investigation [11]. In the previous study significant increase of airway thickness in patients with asthma comparing to healthy subjects was revealed [12].…”
Section: Introductionmentioning
confidence: 99%